Industrialisasi Pendidikan Tinggi - M. Imam Zamroni (Unisia, 2008)
This article aims to decribes that the commercialization and industrialization of state of higher education are some dilemma of government policy’s in the liberalization era. There are challenges and opportunities. At the one hand, industrialization increasing education expenditure, so that the poor people can’t acces it, and the other hand, can deliver advantages in the form of welfare for civitas academics and several investors as conducted by developed countries. On the contrary, high education expenditure contrast with ambitions to realize of Education For All (EFA).Key word: education, industrialization, and commercialization,